Nieminen's law revisited - Villanueva Svensson, Miguel (Baltistica, 2021)
Nieminen’s law was a matter of vowel reduction: in Proto-Baltic word-final *-as was reduced to *-əs and lost its capacity to carry the stress. This accounts for the following facts: 1) accent position in the nominative singular of mobile o-stems (Lith. lángas, OPr. Deywis/Deiws); 2) the io-stem nominative singular *-īs < *-iəs (Lith. ožỹs, OPr. braydis); 3) the Old Lithuanian dative plural -mus < *-məs; 4) accent position in the dative plural of mobile nouns (OLith. langàmus, OPr. waikammans).